Criminal justice in the United States, 1789 - 1939 - Dale, Elizabeth (New histories of American law, 2011)
"This book chronicles the development of criminal law in America, from the beginning of the constitutional era (1789) through the rise of the New Deal order (1939). Elizabeth Dale discusses the changes in criminal law during that period, tracing shifts in policing, law, the courts, and punishment. She also analyzes the role that popular justice - lynch mobs, vigilance committees, law-and-order societies, and community shunning - played in the development of America's criminal justice system. This book explores the relation between changes in America's criminal justice system and its constitutional order"--